E-Commerce and Insurance Internet Marketing: A Business Review from Indian Context - Negi, Dr. Dheeraj; Jain, Mr. Paras (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper deals the conceptual knowledge of search engine marketing (SEM) or e-commerce, literaturereview, current and future aspects of e-commerce in Indian context. This paper discussed about the topmotivator factors of shopping online. The present development would be a valuable addition to researcherand academicians; and useful theory for practitioners, advertisers, and entrepreneurs